Optimisation and molecular dynamics simulation of mangiferin from mahkota dewa (Phaleria macrocarpa) extract in subcritical water extraction process - Nurmaryam Aini, Hashim (2019)
Mahkota Dewa (Phaleria Macrocarpa) is one of the popular herbal plants that possess numbers of bioactive compounds such as mangiferin, saponin and polyphenols. Mangiferin for instance, has various complementary and alternative medicine (CAM) application including antidiabetic, anti-HIV, anti-cancer and immunomodulatory. This study was conducted with the objectives to extract and characterise the mangiferin obtained from subcritical water extraction (SWE) process as well as simulate the molecular interactions behaviour between water and mangiferin. The extraction parameters namely solid to solvent ratios, temperature and time were screened using One-Factor-At-A-Time (OFAT) and followed by optimisation using Box-Behnken design. In screening, the solid to solvent ratios, temperature and time were varied from 30 g/L to 70 g/L, 50 °C to 150 °C and 3 h to 7 h, respectively. In optimisation the process parameters were set at 50 g/L to 70 g/L, 75 °C to 120 °C and 4 h to 6 h which generated total number of 17 experiments including five center points. The extracts were analysed using high performance liquid chromatography (HPLC) for quantification of mangiferin yields and further characterized using liquid chromatography mass spectrometry (LCMS), scanning electron microscopy (SEM), total phenolic content (TPC), antioxidant DPPH radical-scavenging activity and cytotoxicity MTT-assay. The molecular dynamic simulations were performed under NVT ensemble for 1000 ps and NPT ensemble for 1000 ps with time step of 1.0 fs using Accelrys Material Studio® 7.0 software with COMPASS force field. The intermolecular interaction of mangiferin and water were simulated at the temperature of 50 °C, 75 °C, 100 °C, 125 °C and 150 °C, whereas the simulation for optimised condition were compared with literature. The OFAT results show that the highest yield of mangiferin (15.9213 ± 0.11 w/w%) was obtained at 60 g/L, 100 °C, and 5 h. The optimization results show that the developed quadratic model is adequately fitted with the experimental data with R2 and R2adj value of 0.9883 and 0.9722, respectively. The optimum mangiferin yield of 16.5123 w/w% was obtained at solid to solvent ratios of 57.80 g/L, temperature of 106.7 °C and extraction time of 5 h with 1.9 % deviation from predicted mangiferin yield. The total phenolic content value for screened conditions was 122.60 ± 1.07 mg GAE/mg while optimised conditions recorded 124.88 ± 1.09 mg GAE/g. Antioxidant activities for both screened and optimised Mahkota Dewa fruits extracts was found to have moderate reducing power activity (IC50) at 78.85 μg/ml and 63.49 μg/ml, respectively in comparison with ascorbic acid. This study also revealed that both screened and optimised Mahkota Dewa fruits extracts was found to have moderate reducing power activity with value of 28.23 ± 0.184 μg/ml and 25.63 ± 0.193 μg/ml, respectively towards MCF-7 cell line. The findings from molecular dynamic simulation studies shows that the density, radial distribution functions (RDFs) and diffusion coefficient calculated for all system are comparable to the literature and thus verify the method used. A strong hydrogen bonding between solvent-solute can be seen as the temperature increased and led to greater solubility values and it was identified that strong hydrogen bonding formed between mangiferin and water by OH2OHMR4(OH1) interaction. Overall, this study had successfully screened and optimised the extraction of mangiferin from Mahkota Dewa fruits through experimental and computational approach. The outcome is crucial in determining the optimum operating temperature in extracting mangiferin, besides through computer simulation this process has been studied microscopically.